Іntegration of university education teacher of Ukraine into the European educational space (Pedagogy of Higher and Secondary Education, 2012)
Dgelan A. Іntegration of university education teacher of Ukraine into the European educational space.The article deals with the current trends of integration of higher pedagogical education in Ukraine, the content of university teacher training, the creation of a system of teacher training, the learning process in higher educational establishments.
Keywords: higher pedagogical education; universities; learning process; vocational practice; educational space; integration